(untitled) (Journal of Society of Surgeons of Nepal, 2025)
Introduction: Acute appendicitis is a common surgical emergency requiring prompt intervention to prevent complications like perforation and peritonitis. Traditionally, open appendectomy (OA) has been the standard approach, but laparoscopic appendectomy (LA) has become more popular due to faster recovery, reduced pain, shorter hospital stays, and fewer surgical site infections (SSIs). However, the role of LA in perforated cases remains controversial. This study aimed to compare the outcomes of OA and LA in both uncomplicated and perforated appendicitis to determine the optimal surgical approach. Methods: This 24-month retrospective comparative study was conducted at F.H. Medical College & Hospital, Agra, including 108 patients with acute or perforated appendicitis. Patients were randomly divided into two groups: LA (n=54) and OA (n=54). Both procedures were performed under general anaesthesia with prophylactic antibiotics. Outcomes such as operating time, analgesic needs, hospital stay, and postoperative complications were recorded and analysed using SPSS 17.0, with p < 0.05 considered statistically significant. Results: Among 108 patients (54 in each group), laparoscopic and open appendectomy groups were comparable in age (24 vs 23 years), sex distribution, and severity (acute: 30 vs 28; perforated: 14 vs 15). Conversion to open surgery occurred mainly due to failure to progress (3 cases). Laparoscopic appendectomy showed reduced analgesic requirements (parenteral: 1.0 ± 0.5 vs 1.5 ± 0.6; p = 0.001), shorter hospital stay (1.4 ± 0.7 vs 3.4 ± 1.0 days; p < 0.001), and earlier return to normal activity (12.6 ± 3.3 vs 19.1 ± 3.1 days; p < 0.001). Vomiting (16.7% vs 27.8%; p = 0.001) and paralytic ileus (5.6% vs 22.2%; p = 0.04) were significantly higher after open appendectomy. Conclusion: This study findings suggests that laparoscopic appendectomy offered significant advantages over open surgery, including shorter hospital stays, faster recovery times, and reduced analgesic needs.